Synergy of quantita- tive and qualitative marketing research − CAPI and observation diary - Lipowski, Marcin; Pastuszak, Zbigniew; Bondos, Ilona (Synergia ilościowych i jakościowych badań marketingowych – CAPI i samoobserwacja, 2018)
The purpose of the publication is to indicate the need for a well thought-out combination of quantitative marketing research with qualitative research. The result of this research approach should be a fuller understanding of the research problem and the ability to interpret results more closely, while maintaining the reliability of the whole research process. In the theoretical part of the article, the essence of quantitative and qualitative research, with particular emphasis on the limitations and strengths of both research approaches, is presented. The increasing popularity of qualitative research does not absolve researchers from the prudent attitude towards the whole marketing research process − including the need to verify hypotheses or research questions. Excessive simplification in the approach to qualitative research can distort the essence of marketing research. In the empirical part of the article, the authors presented an example of combining quantitative marketing research with qualitative research − for this purpose, the results of their research will be used (scientific grant from National Science Centre). The CAPI technique (n = 1103) was used in the quantitative study, and observation diaries (n = 110) were used for qualitative research
Econometrics = Ekonometria, 2018, Vol. 22, No. 1, s. 58-67
Keywords: marketing research; triangulacja; triangulation; synergy; quantitative research; self-observation; badania marketingowe; synergia; badania ilościowe; samoobserwacja